Peran Pemerintah Desa Sawang Dalam Penanggulangan Bencana Banjir Di Kecamatan Tapin Selatan Kabupaten Tapin - Sya'bani Arlan, Agus (STIA Bina Banua Banjarmasin, 2025)
The Government of Sawang Village, South Tapin District, Tapin Regency as a government institution that is ready for disasters immediately descended on the scene of the disaster. This study uses a qualitative approach with a descriptive-qualitative type, the data collection techniques used are interviews, observations and documentation, data sources are taken through purposive sampling of 11 informants. The results of the first study, from the sub-variables of regulators to help overcome the problem have been running optimally. Second, the sub-variable of the regulator with indicators to facilitate the needs for flood management is not optimal for flood management. Third, the dynamizer sub-variable with indicators as an agent to accelerate changes in the village government has not been optimal and has not been maximized. Fourth, the dynamist sub-variable with indicators as an increase in innovation is not optimal because it has not been implemented properly. Fifth, the facilitator sub-variable with indicators as facilities and infrastructure has not been optimal because development in the village has not been carried out properly. Sixth, the facilitator sub-variable with indicators as the provision of counseling has not been optimal because counseling is very rarely carried out. Seventh, the catalyst sub-variable with indicators as a response to various complaints is optimal because the village government always accommodates various community complaints. Eighth, the catalyst sub-variable with multi-stakeholder coordination indicators is optimal because the village government always involves the community. To optimize the role of the Sawang Village Patrol, South Tapin District, Tapin Regency, it is recommended that the Head of Sawang Village should increase knowledge in the form of technical guidance as a provision in helping people affected by the flood disaster, to the community should get used to and comply with the things recommended by the government. And to employees, further increase the socialization program so that the community is aware of the dangers of flooding. ABSTRAK Pemerintah Desa Sawang Kecamatan Tapin Selatan Kabupaten Tapin sebagai lembaga pemerintah yang siap untuk kebencanaan yang langsung turun ke tempat kejadian bencana. Penelitian ini menggunakan pendekatan kualitatif dengan tipe deskriptif-kualitatif, teknik pengumpulan data yang digunakan adalah wawancara, observasi dan dokumentasi, sumber data diambil melalui penarikan secara purposive sampling berjumlah 11 orang informan. Hasil dari penelitian Pertama, dari sub variabel regulator membantu mengatasi masalah sudah berjalan optimal. Kedua, sub variabel regulator dengan indikator memfasilitasi kebutuhan guna penanganan banjir belum optimal untuk penanganan banjir tersebut. Ketiga, sub variabel dinamisator dengan indikator sebagai agen mempercepat perubahan pemerintah desa belum optimal dan belum maksimal dapat dilaksanakan. Keempat, sub variabel dinamisator dengan indikator sebagai peningkatan inovasi belum optimal karena belum terlaksana dengan baik. Kelima, sub variabel fasilitator dengan indikator sebagai sarana dan prasarana belum optimal karena pembangunan di desa belum terlaksana dengan baik. Keenam, sub variabel fasilitator dengan indikator sebagai penyediaan penyuluhan belum optimal karena penyuluhan sangat jarang dilaksanakan. Ketujuh, sub variabel katalisator dengan indikator sebagai respon berbagai keluhan sudah optimal karena pemerintah desa selalu menampung berbagai keluhan masyarakat. Kedelapan, sub variabel katalisator dengan indikator koordinasi multi pihak sudah optimal karena pemerintah desa selalu melibatkan masyarakat. Untuk mengoptimalkan peran Pemarintahan Desa Sawang Kecamatan Tapin Selatan Kabupaten Tapin maka disarankan kepada Kepala Desa Sawang hendaknya meningkatkan pengetahuan berupa bimbingan teknis sebagai bekal dalam membantu masyarakat yang terdampak bencana banjir, kepada masyarakat hendaknya membiasakan dan mematuhi hal-hal yang dianjurkan pemerintah. Dan kepada pegawai lebih meningkatkan program sosialisasi agar masyarakat sadar terhadap bahaya banjir.